2011
DOI: 10.1016/s0973-0508(11)80018-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of head injury in unknown patients at Level-1 apex trauma centre

Abstract: This was a retrospective study, carried out at the Department of Neurosurgery at Jai Prakash Narain Apex Trauma Centre (JPNATC), All India Institute of Medical Sciences (AIIMS), New Delhi. Many patients with head injury whose identity cannot be ascertained, are admitted in our hospital. Care and management of these neglected patients from pre-hospital till discharge, rehabilitation or death is fraught with many challenges. Very few studies in world literature are available on this subgroup of patients. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…RTA constitutes the main cause of TBI, possibly because of urbanization and industrialization; moreover, youngsters take pride in living a high adrenaline rush life, driving rash and fast. The data was consistent with studies done in the past by Saxena et al 11 and Nath et al 10 TBI is more difficult to assess. The clinical examination is of restricted value during the first hours and days after a head injury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…RTA constitutes the main cause of TBI, possibly because of urbanization and industrialization; moreover, youngsters take pride in living a high adrenaline rush life, driving rash and fast. The data was consistent with studies done in the past by Saxena et al 11 and Nath et al 10 TBI is more difficult to assess. The clinical examination is of restricted value during the first hours and days after a head injury.…”
Section: Discussionsupporting
confidence: 92%
“…TBI poses the substantial burden of disability and death occurring in low-and middle-income countries. In studies by Gururaj et al 9 and Nath et al, 10 the majority of TBI patients were in their 3rd decade with a male preponderance; likewise in our study, we had a male:female ratio of 1.9:1 and maximum patients in their 3rd decade. RTA constitutes the main cause of TBI, possibly because of urbanization and industrialization; moreover, youngsters take pride in living a high adrenaline rush life, driving rash and fast.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…11 Ahmad FU et al also showed majority of patients were in between 25 to 40 years of age group. The above fact is also evident in present study as majority of victims are males (94.38%) with mean age of 29.89 years.…”
Section: Discussionmentioning
confidence: 91%
“…This signifies severity of the injury at the time of presentation. Poor GCS score is associated with worse prognosis (15) . Also in this study, the pupils were unreactive in 29 cases (46.1%) and were reactive in 34 cases (53.9%).…”
Section: Resultsmentioning
confidence: 99%